Training on the Application of Silage Technology for Vegetable Waste as Feed for Ducks in Kayu Manis Village - Suningsih, Nining; Hakim, Muhammad; Nur'aini, Nur'aini (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This study addresses the challenge of low community knowledge in Kayu Manis village, aiming to boost interest and skills in duck farming. The primary objective is to elevate community understanding by applying silage technology to convert vegetable waste into duck feed. Method: Through training sessions involving socialization, practical demonstrations, and hands-on practice, participants learn to create vegetable waste silage as duck feed. Pre- and post-test evaluation reveals significant sequential improvements of 88.15%, 7.69%, and 89.23% in knowledge, interest, and skills. Practical Applications: The outcomes offer practical benefits for the community and potential scalability for similar agricultural sectors. Silage technology proves valuable in enhancing sustainable farming practices. Conclusion: In conclusion, the community-based intervention focusing on making vegetable waste silage effectively achieves its goals of enhancing participants' knowledge, interest, and skills in duck farming. The sequential increases of 88.15%, 7.69%, and 89.23% underscore the training program's success. The practical applications extend beyond Kayu Manis village, demonstrating the broader relevance and impact of implementing silage technology in agricultural practices. This research contributes significantly to addressing the initial problem outlined in the introduction, emphasizing the importance of sustainable and innovative approaches in community-based agrarian interventions.